Energy, Protein, Fat and Carbohydrate Intakes in Children with Wasting Syndrome at SDN 2 Tlanak Kedungpring, Lamongan District - Ifta Nur Fadhilah; Inne Soesanti; Mujayanto; Nur Hatijah (Journal of Nutrition Explorations, 2024)
In school-age children, the body will later need energy and macronutrients for growth, physical activity and other skills. The purpose of this study was to describe the energy, protein, fat and carbohydrate intakes in children with wasting syndrome at SDN 2 Tlanak Kedungpring, Lamongan Regency. The research design used is descriptive observational. The sample consisted of 30 respondents. The technique used was 2 x 24-hour food recall interviews. The research time starts from October 2022-March 2023. The analysis technique used is univariate or descriptive. The results of this study showed that 20 respondents (66.6%) had energy consumption levels in the severe deficit category, 28 respondents (93.3%) had carbohydrate consumption levels in the severe deficit category, 13 respondents (43.4%) had protein consumption in the category of weight deficit and as many as 13 respondents (43.4%) had a level of fat consumption in the normal category. The conclusion of the study was that most children with wasting syndrome had normal levels of energy, carbohydrate and protein intake, deficits in weight and fat. The hope of this study is to provide an impetus for parents and the school to pay attention to children's food so that nutritional needs can be met.